Translation Techniques of Legalese Archaisms: Evaluating Human Expertise, Machine Power, and Artificial Intelligence - Islakhiyah, Islakhiyah; Cholsy, Hayatul (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2025)
Translation of legalese archaisms considered as a bedrock on comprehending the content of deed agreement in legal documents. Since society has been so close to digitalization, they often use machine translation and artificial intelligence as a tool assisted on translation, resulting in discrepancies of the meaning and nuance contained in the archaisms of source language. Departing from this, this research aims to describe the common inclination used on the translation technique of legalese archaisms in legal documents and its implication. This research uses a qualitative descriptive approach. The data of this research are obtained from three legal documents; Power of Attorney, Deed of Termination, and Memorandum of Understanding. The data collected by using the close observation techniques. Afterwards, the data will be analyzed using the translation techniques by Molina and Albir (2002), and the translation designation theory by Lawrence Venuti (1995) to find out the common inclination on the translation results of these three variables. After conducting a thorough analysis on the translation techniques, the researchers concluded that the translation of the legalese archaisms by machine power and artificial intelligence applied foreignization as the common inclination on the translation process. On the contrary, the translation result of human expertise applied domestication as the common inclination.